STRATEGIES AND DIFFICULTIES IN THE TRANSLATION OF IT TERMINOLOGY - Василевська, Тетяна (SWorldJournal, 2025)
The article examines the features and strategies of translating IT terminology into Ukrainian. Based on the analysis of linguistic and translation literature, as well as examples from modern sources, the structural and semantic characteristics of IT term